Analisis Sensitivitas Premi Asuransi Jiwa Terhadap Usia dan Tingkat Suku Bunga Berdasarkan Data Life Table dari World Health Organization - Miftahul Jannah; Maharani Renika Putri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the sensitivity of life insurance premiums to changes in age and interest rates using mortality data from the World Health Organization (WHO). The data used is the 2015 Adult Mortality data obtained from the Global Health Observatory Data Repository and processed into the probability of death (qx) using a simple exponential model approach. Premium calculations are performed using the present value concept, taking into account variations in interest rates of 3%, 5%, and 7%, as well as an age range of 25 to 50 years. The analysis was conducted to examine the effect of changes in age and interest rates on the resulting premium amount. The results show that age has a positive and dominant effect on premiums, with increasing age leading to a significant increase in premiums. Conversely, interest rates have a negative effect on premiums, with increasing interest rates leading to a decrease in premiums. However, the effect of interest rates is relatively smaller compared to age. This study demonstrates that mortality is a major factor in determining life insurance premiums. Furthermore, the simple approach used in this study provides a clear picture of the relationship between demographic and economic factors in premium determination.